1. "P" is an assumed variable as a point of view of the observer.

2. (P=P) leads to an infinite regress as ((((P=P)=(Q=Q))=(R=R))=(S=S))=....

3. (P=P) has the same premise as the conclusion thus is circular.

1. "P" is an assumed variable as a point of view of the observer.

2. (P=P) leads to an infinite regress as ((((P=P)=(Q=Q))=(R=R))=(S=S))=....

3. (P=P) has the same premise as the conclusion thus is circular.

2. (P=P) leads to an infinite regress as ((((P=P)=(Q=Q))=(R=R))=(S=S))=....

3. (P=P) has the same premise as the conclusion thus is circular.